Chestnut trees in bloom and rowers on the canal in Regent's Park, London, England - Murrow, Janet Brewster (Tufts Archival Research Center, 2014)
This date is approximate. negatives (photographic). Photograph appears in photo album, MS225.002.00018, p. 003